The Effectiveness of the KOMPAK Learning Model in Enhancing Learning Engagement among Children with Autism Spectrum Disorder in Inclusive Elementary Schools - Tuti Haryati; Pamuji Raharjo; GH Sugeng Koco Purnomo; RA Sri Turwati Sulasminingsih (Jurnal Pendidikan Terapan, 2026)
Purpose: This study examines the effectiveness of the KOMPAK Learning Model in improving learning engagement among children with Autism Spectrum Disorder (ASD) in inclusive elementary school settings. The investigation focuses on three core components of engagement attention, active participation, and responsiveness to instructional cues which frequently present challenges for students with ASD during classroom learning. Methods: A quantitative approach employing a one-group pretest–posttest quasi-experimental design was used. Thirty children diagnosed with ASD were selected through purposive sampling. Learning engagement data were gathered using an observational instrument previously validated for reliability. A paired-sample t-test was conducted to compare engagement levels before and after implementation of the KOMPAK model. Findings: The results indicate a statistically significant increase in learning engagement within the sample following the intervention. Mean scores rose from 56.30 at pretest to 78.45 at posttest. The paired-sample t-test yielded p < 0.001, and the effect size (d = 0.85) fell within the large range. While these findings suggest that the KOMPAK Learning Model may enhance attention, participation, and responsiveness among students with ASD, they should be interpreted within the limitations of a single-group design. Research implications: The study provides preliminary empirical support for the KOMPAK Learning Model as an adaptive instructional strategy in inclusive elementary schools. Its application may assist teachers in fostering more consistent engagement among students with ASD, thereby contributing to improved inclusive learning quality and supporting students’ social–academic development. Originality: This research contributes to the field of inclusive education by offering empirical evidence on a learning model tailored to the distinct characteristics of children with ASD. Its emphasis on learning engagement rather than solely academic or behavioral outcomes distinguishes it from prior studies.